Breast acinic cell carcinoma with weak progesterone receptor expression: a case report and literature review - Bai, Caiyun; Xin, Xiaodong; Yang, Yisen; Qu, Fengjiang; Fan, Zhimin (Frontiers in Oncology, 2025)
RationaleAcinic cell carcinoma (AcCC) of the breast is an extremely rare malignant epithelial tumor characterized by acini cell differentiation, clinical low-grade malignancy, and a molecular triple-negative subtype.Patient concernA 47-year-old female presented with a 1-month history of a painless mass in her right breast.DiagnosisUltrasound imaging, mammography and magnetic resonance imaging revealed a lesion, approximately 3.0cm×1.5cm in size, in the right breast, which was considered to be a malignancy. After the surgery, the AcCC of the breast was confirmed histologically.InterventionsRight breast mastectomy and sentinel lymph node biopsy were performed. Adjuvant chemotherapy included 4 cycles of doxorubicin hydrochloride (Adriamycin) and cyclophosphamide followed by 4 cycles of docetaxel (Taxotere).OutcomesThe patient was discharged from the hospital after surgery. There was no sign of recurrence during a 9-month follow-up period.LessonsAcinic cell carcinoma (AcCC) of the breast is an extremely rare malignant epithelial tumor that can be accurately diagnosed based on histopathologic morphology and immunohistochemistry. The weak positive progesterone receptor (PR) expressed in this case is extremely rare, which may provide a new research direction for the endocrine therapy of AcCC. Both AcCC and microglandular adenosis(MGA) exhibit microglandular growth, and the relationship between them remains unclear. Differentiation between them not only relies on histomorphology and pathological immunohistochemistry but also depends on clinical manifestations and other presentations. Optimal treatment of AcCC is the same as that for invasive breast cancer. The prognosis is generally good, with adjuvant therapy after surgery.